Perbandingan Sampling dengan Metode Test Pit dan Pengeboran pada Endapan Bauksit PT. Prima Abadi Mineral Kabupaten Ketapang Provinsi Kalimantan Barat - idris herkan afandi (JURNAL SIMETRIK, 2019)
Resource estimation are related to the quality of samples in the field. One of sampling bauxite method is a test pit. However, sufficiently deep deposition conditions become a constraint related to security in retrieval by this method. Therefore, researchers suspect that bauxite sampling can also be done by drilling with results that are not much different from making test pits. the aim of this study was to compare bauxite sampling with with test pits and drilling seen from the engineering work, cost efficiency, time and quality of the sampling produced.The research was conducted at PT. Harita Prima Abadi Mineral Ketapang by observing the sampling process and interviewing workers. It was obtained that the cost of making 1 (one) test pit was Rp. 5.000.000, and the cost of 1 (one) drilling is Rp. 2.000.000. The time fore making a test pit to minimal 3 workers is 6-8 hours and the drilling time to minimal 4 workers is 3-4 hours. The quality of bauxite samples from test pit is very good, the umber of samples can be taken as needed. While the quality of drilling samples is CF cannot be calkulated and bauxite samples obtained have a small size and a little amount.